Clinical Outcomes after Intravenous Alteplase in Elderly Patients with Acute Ischaemic Stroke: A Retrospective Analysis of Patients Treated at a Tertiary Neurology Centre in England from 2013 to 2018 - Xuya Huang; Phillip Nash; Vafa Alakbarzade; Brian Clarke; Anthony C. Pereira (Stroke Research and Treatment)
Intravenous thrombolysis with alteplase within 4.5 hours from symptom onset is a well-established treatment of acute ischaemic stroke (AIS). The aim was to compare alteplase for AIS between patients aged >80 and ≤80 years in our registry data, from 2013 to 2018. Mechanical thrombectomy cases were excluded. We assessed clinical outcomes over the six-year period and between patients aged over 80 and ≤80 years, using measures including the discharge modified Rankin Scale (mRS), 24-hour National Institutes of Health Stroke Scale (NIHSS) improvement, and symptomatic intracerebral haemorrhage (sICH) rate. Of a total of 805 AIS patients who received intravenous alteplase, 278 (34.5%) were over 80 years old, and 527 (65%) were younger. 616 (76.5%) received thrombolysis≤3 hours after symptom onset and 189 (23.5%) within 3-4.5 hours. Median baseline mRS and NIHSS of the elderly cohort were 1 (IQR 0-5) and 13 (IQR 2-37), respectively, compared to the younger cohort 0 (IQR 0-5) and 9 (IQR 0-29). The sICH rate was 7.2% in the elderly and 4.6% in those ≤80 years, p=0.05. NIHSS improved within 24 hours in 34% of the elderly cohort compared to 35% in the younger cohort. At hospital discharge, the mortality rate was 9% in the elderly cohort compared to the 6% in the younger cohort, p=0.154. 25% of patients aged >80 years had mRS≤2 compared to 47% in the younger patients (p<0.0001). In conclusion, thrombolysis in elderly patients results in clinical improvement comparable to younger patients.